Pengaruh Pemberian Perasan Jeruk Nipis Madu terhadap Emesis Gravidarum pada Ibu Hamil Trimester 1 di PMB INA Tjahjanti - Rafiqa Nur Indriani; Rani Safitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Nausea and vomiting in the first trimester of pregnancy are common and can interfere with the mother's ability to eat and feel comfortable. One more economical and low-risk alternative is to use natural remedies such as lime juice and honey in non-pharmacological therapy. In this study, we examined the effectiveness of giving lime juice and honey to relieve symptoms of nausea and vomiting in pregnant women in the first trimester. The design used was a pre-experiment with 30 participants and a one-group pretest-posttest method. The intervention was a glass of fresh lime juice as much as 30 milliliters, one spoon of honey, and 250 milliliters of water given twice a day for seven days. Data analysis was performed using the Wilcoxon test. With a p value of 0.000 (α <0.05), the results showed a significant decrease in the frequency of nausea and vomiting after the intervention, and the majority of participants reported improvement in nausea symptoms. These findings provide clinical evidence that the combination of lime juice and honey can reduce symptoms of emesis gravidarum.